الرقابة الاستراتيجية و أثرها على زيادة فعالية أداء المنظمات - عبد اللطيف, عبد اللطيف; تركمان, حنان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
الرقابة الاستراتيجية هي نظام للتعرف على مدى تنفيذ استراتيجيات المنظمة , أي مدى نجاحها في الوصول إلى أهدافها و غاياتها . و هذا يحتاج إلى وضع خطة استراتيجية و السعي لتنفيذها من أجل تحقيق رسالة المنظمة و أغراضها . يتناول البحث مفهوم الرقابة الاستراتيجية و أهميتها و مستويات الرقابة و مجالاتها و خطوات الرقابة الاستراتيجية و ميزاتها , و يتضمن أيضاً دراسة تحليلية مقارنة لأنظمة الرقابة في كلٍ من مشفى الأسد الجامعي و المشفى الوطني في مدينة اللاذقية . و انتهى البحث إلى استعراض عدد من النتائج و التوصيات المهمة مع إشارة إلى المراجع المستخدمة . Strategic control is a system for determining the extent to which the organization strategies are successful in reaching its goals and objectives , This requires a strategic plan and implementation for organization Mission and goals . The research studies the concept of strategic control and its importance and control level and its area and steps for strategic control . The research also contains an analytical comparative survey for systems of control in Al-Assad Hospital and National Hospital in Latakia . Finally , we conclude the research by resuming the most important results , and offer some recommendations and a list of references on which we relied